MENGAPA PARTAI ISLAM BELUM PERNAH MENANG?: PATH DEPENDENCE REPETITION KEKALAHAN PARTAI ISLAM INDONESIA DALAM PEMILU LEGISLATIF 1955 HINGGA 2019 - Riyanto, Agus (Jurnal Politik Profetik, 2020)
Sociologically, Indonesia is a country with the largest Muslim population in the world, however no Islamic party has ever won the legislative electoral since the Old Order. There are limited research which link the defeat of Islamic parties with their own history as a context. This study uses the perspective of historical institutionalism, particularly the analysis of path dependencies and critical junctures to analyze the defeat of Indonesian Islamic parties by linking the past political decisions in a critical junctures framework. This study has two main findings. First, the defeat of Indonesian Islamic parties during 1955 to 2019 elections was the result of a causal mechanism which was related to political decisions in moments of critical junctures. The mechanism had a significant effect on the path of development of Islamic parties and led to the outcome of defeat. Second, the defeat of the Indonesian Islamic party indicates a path of dependence repetition which includes three process dependence paths triggered by three critical moments in the form of political decisions of party agents. Each resulted in a series of causal follow-up events in the aftermath of critical juncture, which were the process of reactive sequences, reinforcement or self-reinforcing sequences, as well as reinforcement or self-reinforcing sequences and reactive sequences, and put Islamic parties on a certain development path towards the final outcome of the legislative election defeat.